Evaluation of Evidence-Based Nursing Pain Management Practice - Song, Wenjia (Pain Manag Nurs, 2015)
BACKGROUND: It is important to ensure that cancer pain management is based on the best evidence. Nursing evidence-based pain management can be examined through an evaluation of pain documentation. AIMS: This study aimed to (a) modify and test an evaluation tool for nursing cancer pain documentation, and (b) describe the frequency and quality of nursing pain documentation in one oncology unit via electronic medical system. DESIGN AND SETTING: A descriptive cross-sectional design was used for this study at an oncology unit of an academic medical center in the Pacific Northwest. METHODS: Medical records were examined for 37 adults hospitalized during April and May of 2013. Nursing pain documentations (N = 230) were reviewed using an evaluation tool modified from the Cancer Pain Practice Index to consist of 13 evidence-based pain management indicators, including pain assessment, care plan, pharmacologic and nonpharmacologic interventions, monitoring and treatment of analgesic side effects, communication with physicians, and patient education. Individual nursing documentation was assigned a score from 0 (worst possible) to 13 (best possible), to reflect the delivery of evidence-based pain management. RESULTS: The participating nurses documented 90% of the recommended evidence-based pain management indicators. Documentation was suboptimal for pain reassessment, pharmacologic interventions, and bowel regimen. CONCLUSIONS: The study results provide implications for enhancing electronic medical record design and highlight a need for future research to understand the reasons for suboptimal nursing documentation of cancer pain management. For the future use of the data evaluation tool, we recommend additional modifications according to study settings.